PENGUJIAN BAHAN BAKAR GAS PADA MESIN SEPEDA MOTOR KARBURATOR DITINJAU DARI ASPEK TORSI DAN DAYA - Topan Frans Saputra; Arijanto Arijanto (JURNAL TEKNIK MESIN, 2015)
Fossil fuels are a very important source of energy in everyday life, especially in the field of transport and are non-renewable energy sources, while existing data obtained when these vehicles circulating in Indonesia reached 80 million units, of which 85 per cent of this amount is a motorcycle with a majority using the engine carburetor. This experiment aimed to test alternative fuels fuel oil fuel is fuel gas. After testing it was found that the best torque produced fuel LPG gas is 8.20 Nm 7.82 Nm and blue gas at 4000 rpm rotation. The best power generated fuel gas is 2.10 kW and blue gas was 2.06 at 5000 rpm rotation. For the rate of fuel consumption pertamax more fuel efficient than the gas at any rpm the test. As for the fuel efficiency of LPG gas reached 43.94%, pertamax 61.26% at 5000 rpm rotation, and 43.12% blue gas at 4000 rpm rotation